Status Hukum Rumah Apung dalam Perspektif UUPA: Menuju Kepastian Hukum Masyarakat Pesisir - Zulfa, A'immatuz; Perwitasari, Dita; Siswanto, Heru (Notarius, 2026)
ABSTRACTThis study analyzes the regulatory gaps related to floating housing in Indonesia in terms of the UUPA, which is limited to conventional land rights without extending to buildings on water. Using a normative juridical method with a legislative and comparative legal approach, this study aims to analyze whether settlements on water can be granted land rights as mandated by the UUPA and compare it with other countries regarding legal certainty and recognition of floating housing. The results reveal that the regulatory gap creates uncertainty regarding ownership, licensing, and taxation for floating homeowners. This study recommends the establishment of the Right to Water (HAP) and integrated cross-sectoral regulations as a solution to achieve legal certainty, social justice, and sustainable development of coastal settlements.Keywords: Floating Houses; UUPA; Water Rights; Agrarian Law; Legal Certainty.ABSTRAKPenelitian ini menganalisis kesenjangan regulasi terkait rumah apung di Indonesia ditinjau dari UUPA, yang cakupannya terbatas pada hak pertanahan konvensional tanpa menjangkau bangunan di atas perairan. Menggunakan metode yuridis normatif dengan pendekatan perundang-undanganan dan perbandingan hukum, tujuan penelitian ini untuk menganalisa apakah permukiaman di atas air depat diberikan hak atas tanah sesuai diamanatkan UUPA serta membandingkan dengan negara lain terhadap kepastian hukum dan pengakuan tentang rumah apung. Hasil penelitian mengungkapkan bahwa kekosongan regulasi menimbulkan ketidakpastian kepemilikan, perizinan, dan perpajakan bagi pemilik rumah apung. Penelitian ini merekomendasikan pembentukan Hak Atas Perairan (HAP) dan regulasi terpadu lintas sektor sebagai solusi mewujudkan kepastian hukum, keadilan sosial, dan pembangunan berkelanjutan permukiman pesisir.Kata Kunci: Rumah Apung; UUPA; Hak atas Perairan; Hukum Agraria; Kepastian Hukum.